Research on Surface Treatment of Magnesium Alloy and Its Wettability with Resin. Issue 10 (2nd July 2016) - Hu, F. P.; Qin, J.; Zeng, Q. W.; Wang, F.; Zhang, X.; Zhang, N. Y.; Wang, S. Z.; Huang, P.; Fan, Z. H.; Peng, X. D.; Xie, W. D.
Abstract : After phosphatising disposal, the micro-morphology of the AZ31B sheet was observed. The contact angle of the sheet was measured. The surface energy of the sheet was calculated. The laminated sheet was prepared, with preliminary study of its performance. Results showed that the amount and grain size of phosphate were influenced by the phosphating process, as well as wettability of materials. After 30°C/5 min phosphating, a dense phosphating film consisting of zinc phosphate was obtained, and the advancing contact angle of magnesium alloy was 58.3°. Compared with 31.5 mN m −1 of the raw magnesium alloy sheet, the surface energy of the sheet after phosphating reached 90 mN m −1 . The laminated sheet of fibre/resin–phosphated magnesium alloy–fibre/resin has good bonding interface, corrosion resistance and mechanical properties.